Subserosal adenomyotic cysts and peritoneal inclusion cysts – Unusual differential diagnoses of multicystic pelvic masses: A review of two cases - H.K. Angeline Chua; S.Y. Charissa Goh; Varuni Upamali; Meei Jiun Seet; P.C. Adele Wong; W.L. Jessie Phoon (Case Reports in Women's Health, 2020)
Background: Multiloculated pelvic cysts are commonly misdiagnosed as ovarian tumors or malignancies. We report 2 patients diagnosed with subserosal adenomyotic cysts and peritoneal inclusion cysts, mimicking multiloculated pelvic tumors. We discuss their clinical presentation, investigations, operation findings, and histopathology, present a literature review. Cases: Case 1 was a 44-year-old patient with abnormal uterine bleeding. Imaging showed an enlarging multiloculated cystic structure over the right uterine wall. She underwent a diagnostic laparoscopy and right salpingo-ophorectomy. Intra-operatively, she was found to have multiple subserosal uterine cysts, diagnosed as adenomyotic cysts on histology.Case 2 was a 50-year-old patient with history of laparoscopic cystectomy done 20 years ago. She was incidentally found to have a multiloculated cystic lesion in the pelvis. The lesion was located midline, anterior and superior to the uterus and bladder. She underwent a total abdominal hysterectomy, bilateral salpingo-ophorectomy, and bladder peritonectomy. Intra-operatively, multiple cystic lesions were noted over the anterior and fundus of uterus, bladder peritoneum, and pelvic side walls. The condition was confirmed to be peritoneal inclusion cysts on histology. Conclusion: Subserosal adenomyotic cysts are a rare presentation of adenomyosis. They typically occur in premenopausal women. Treatment is usually by hormonal medications or surgical excision.Many patients with peritoneal inclusion cysts have a history of peritoneal insults. Surgical excision is the most commonly described management as they often mimic malignancy. Both conditions are unusual presentations of multiloculated pelvic masses. A high recurrence rate is found, hence long-term follow-up with imaging is essential.